Sustainability Report and the Legitimisation of Business: Environmental disclosure in BP and Shell - Faraoni, Valentina (2013)
Much of the literature on corporate reporting has explained the disclosure of information about environmental issues as a strategy to legitimise an organisation’s operations. Consequentially, the evident concern over the eco-systems and the continuing expansion of the companies’ business in environmental high-risk industries, such as the energy sector, questions how organisations obtain their licence to operate through disclosure. Based on the analysis of the sustainability reports published by BP and Shell, the purpose of this thesis is to illustrate how the strategies of disclosure undertaken by corporations reply to the society’s expectations regarding corporate activities, in order to achieve the status of legitimacy. The method adopted investigates twelve sustainability reports from 1990s and 2000s by BP and Shell through discourse analysis. The different strategies undertaken by the companies to legitimise their operations are reported. The findings suggest that the strategies differs according to the determined socio-political context and environmentally threatening events that characterise an historical period, which influence how society perceives corporate actions. The study confirms the strict relationship between corporations and the society and implies the consideration of external expectations when dealing with the status of legitimacy.